Tariff protection and trade agreements - Medrano, Leonardo (Estudios Económicos de El Colegio de México, 1999)
This paper studies the optimal tariff rates on goods imported from the rest of the world when a commercial club accepts a new partner. It shows that when a new member is accepted into the club, the other members of a free trade agreement have incentives to reduce tariffs on the rest of the world's goods. However, when the trade agreement is a custom union, the union may have incentives to increase the common external tariff. This happens when the industry of the custom union is small compared to the world industry.